Dielectric Properties of Calcium Phosphate Ceramics - Kaygili, Omer; Keser, Serhat; Ates, Tankut; Kirbag, Sevda; Yakuphanoğlu, Fahrettin (Kaunas Univ Tech, 2016)
Calcium phosphate ceramics with various Ca/P ratios of 1, 2, 3, 4 and 8 were synthesized via sol-gel route. The effects of Ca/P molar ratio on structural, morphological and dielectric properties were investigated in detail using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy and dielectric measurements. The Ca/P molar ratio significantly affects the crystal structure and phase composition. The crystallite size, lattice parameters and volume of the unit cell were remarkably affected by the change in the Ca/P molar ratio. The microstructure is changed with increasing the Ca/P molar ratio. The relative permittivity and alternating current conductivity gradually decrease for the samples having the Ca/P ratios higher than 2. The dielectric loss decreases gradually with the increase of the molar ratio of Ca/P.
Keywords: calcium phosphates; crystal structure; dielectric properties